PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN TALAOK BAYANG - Lisri Wahyuni, Jumetri; Aima, Zulfitri; Pratiwi, Merina (Pendidikan Matematika, 2014)
ABSTRACTThis research was designed for revealing whether understanding of mathematical concept by Guided Teaching active learning strategy was better than that by using conventional learning in class VIII of MTsN Talaok Bayang. This was an experimental research which used random toward the subject design. In collecting the data, an essay test on the conceptual understanding was used. The data collected was analyzed by using t-test. Based on the result of data analysis, it was found that the two sample classes were normally distributed and homogenous. the result of hypothesis test showed that the understanding of mathematical concepts by Guided teaching active learning strategy was better than that by using conventional learning in class VIII of MTsN Talaok Bayang